The Implementation of School Based Management in Primary School - Haryanti, Eliza; Harapan, Edi; Kesumawati, Nila (Yayasan Sembilan Pemuda Indonesia, 2021)
This study aims to review and describe the school based management in Madrasah Ibtidaiyah Ilir Timur II in Palembang. This is descriptive qualitative research. The subject was teachers in Madrasah Ibtidaiyah Riyadhul Janah Palembang. Data in this study was collected by interviews and analyzed using triangulation. The results stated that school based management will take place effectively and efficiently when supported by human resources professional to operate schools, sufficient funds, so schools are able to hire staff in accordance with its function, infrastructure to support the process, parents and community support significantly better in thought and favors a significant contribution.